Primary lung cancer in women after previous breast cancer. Issue 6 (18th January 2022) - Nobel, Tamar B; Carr, Rebecca A; Caso, Raul; Livschitz, Jennifer; Nussenzweig, Samuel; Hsu, Meier; Tan, Kay See; Sihag, Smita; Adusumilli, Prasad S; Bott, Matthew J; Downey, Robert J; Huang, James; et al.
Abstract: Background: Breast cancer is the most common malignancy among women in the USA. Improved survival has resulted in increasing incidence of second primary malignancies, of which lung cancer is the most common. The United States Preventive Services Task Force (USPSTF) guidelines for lung-cancer screening do not include previous malignancy as a high-risk feature requiring evaluation. The aim of this study was to compare women undergoing resection for lung cancer with and without a history of breast cancer and to assess whether there were differences in stage at diagnosis, survival and eligibility for lung-cancer screening between the two groups. Methods: Women who underwent lung-cancer resection between 2000 and 2017 were identified. Demographic, clinicopathological, treatment and outcomes data were compared between patients with a history of breast cancer (BC- Lung) and patients without a history of breast cancer (P-Lung) before lung cancer. Results: Of 2192 patients included, 331 (15.1 per cent) were in the BC- Lung group. The most common method of lung-cancer diagnosis in the BC- Lung group was breast-cancer surveillance or work-up imaging. Patients in the BC- Lung group had an earlier stage of lung cancer at the time of diagnosis. Five-year overall survival was not statistically significantly different between groups (73.3 per cent for both). Overall, 58.4 per cent of patients (1281 patients) had a history of smoking, and 33.3 per cent (731 patients) met the current criteria for lung-cancer screening. Conclusion: Differences in stage at diagnosis of lung cancer and treatment selection were observed between patients with and without a history of breast cancer. Overall, there were no statistically significant differences in genomic or oncogenic pathway alterations between the two groups, which suggests that lung cancer in patients who previously had breast cancer may not be affected at the genomic level by the previous breast cancer. The most important finding of the study was that a high percentage of women with lung cancer, regardless of breast-cancer history, did not meet the current USPSTF criteria for lung-cancer screening. Abstract : Differences in stage at diagnosis of lung cancer and treatment selection were observed between patients with and without a history of breast cancer. Overall, there were no statistically significant differences in genomic or oncogenic pathway alterations between the two groups, which suggests that lung cancer in patients who previously had breast cancer may not be affected at the genomic level by the previous breast cancer. The most important finding of the study was that a high percentage of women with lung cancer, regardless of breast cancer history, did not meet the current USPSTF criteria for lung cancer screening.